2017
DOI: 10.1111/acer.13560
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet Suppresses Alcohol Withdrawal Syndrome in Rats

Abstract: Our preclinical pilot study suggests that a ketogenic diet may be a novel approach for treating alcohol withdrawal symptoms in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
2
29
2
Order By: Relevance
“…For example, it is unclear if a diet high in fat is necessary to trigger reduced alcohol drinking behavior or if a diet high in sugar would induce the same effect. While a recent study showed a reduction of alcohol withdrawal syndrome following a high fat/ketogenic diet intake [62], studies exist demonstrating that excessive consumption of palatable/sweet food could curb alcohol drinking behavior in human alcoholics [10,11] which also agrees with the Alcoholics Anonymous recommendation of eating more sweet/palatable food to reduce alcohol craving [63]. These data collectively suggest that palatable food may compete with propensity to drink alcohol as both are capable of interacting with the brain reward circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is unclear if a diet high in fat is necessary to trigger reduced alcohol drinking behavior or if a diet high in sugar would induce the same effect. While a recent study showed a reduction of alcohol withdrawal syndrome following a high fat/ketogenic diet intake [62], studies exist demonstrating that excessive consumption of palatable/sweet food could curb alcohol drinking behavior in human alcoholics [10,11] which also agrees with the Alcoholics Anonymous recommendation of eating more sweet/palatable food to reduce alcohol craving [63]. These data collectively suggest that palatable food may compete with propensity to drink alcohol as both are capable of interacting with the brain reward circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that in addition to lactate, chronic EtOH exposure increases the production of ketone bodies (Kreisberg, ). Ketogenic diets and ketone supplementation have been demonstrated to improve memory, enhance hippocampal long‐term potentiation, and reduce the severity of EtOH withdrawal syndrome (Dencker et al., ; Hernandez et al., ; Newman et al., ). Similarly, astrocyte‐neuron lactate transfer is necessary for long‐term memory formation and long‐term potentiation (Suzuki et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…97 The concomitant consumption of a KD exacerbates the risk, and it is therefore to be recommend against the prescription of a KD to those with a history of alcohol and substance abuse where relapse seems possible, especially in the absence of adequate support. Noteworthy, a ketogenic diet seems to be effective in suppressing alcohol cravings both at a preclinical level and in subjects with obesity, 98,99 although it should be kept in mind that the physiology underlying such association might be very different across species, as the link in rodent models seems to be an elevation in Fibroblast Growth Factor 21 levels, 78,100 whereas such elevation following a ketogenic diet is not observed in human beings. 101…”
Section: Frail Elderly Patients History Of Mental Disorders and Sumentioning
confidence: 99%